Tribological and mechanical properties of AA6061 reinforced with SiC and graphite for automobile applications. (2020) - Padmavathy, S.; Kamalakannan, R.; Manikandan, A.
Abstract: The main objective of this work to reduce the wear rate of the brake drum material used for braking purpose. Aluminium alloy of AA6061 is reinforced with the reinforcement materials of Silicon Carbide and Graphite in the various proportions to study the Tribological Properties and Mechanical properties for the application of Automobiles. After the fabrication of composite material for the brake drum is tested by using pin-on disc equipment for friction wear and hardness is measured by using Impact test. SEM analysis is carried out to view the image of mixing of Proportions evenly in the fabricated material.